2023
DOI: 10.3390/life13020331
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Blue Light (420 nm) Reduces Metabolic Activity and Inhibits Proliferation of Human Dermal Fibroblasts

Abstract: Hypertrophic scarring in burn wounds is caused by overactive fibroblasts and myofibroblasts. Blue light reveals wavelength- and dose-dependent antibacterial and antiproliferative effects and may serve as a therapeutic option against wound infection and fibrotic conditions. Therefore, we evaluated in this study the effects of single and multiple irradiations with blue light at 420 nm (BL420) on the intracellular ATP concentration, and on the viability and proliferation of the human skin fibroblast (HDFs). In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Blue light has been demonstrated to be beneficial for treating acute and chronic skin wounds, reducing inflammation, and promoting tissue regeneration [ 27 ]. Other studies have also reported that blue light holds some promise, particularly in the fight against excessive scarring and wound infections; however, it is crucial to consider the potential toxic and antiproliferative effects and to carefully consider the benefits and risks of using blue light to minimise the disturbances of skin physiology, which could result in impaired wound healing/closure and decreased scar breaking strength [ 28 ]. In this present study, a wavelength of 660 nm and a fluence of 5 J/cm 2 was used.…”
Section: Discussionmentioning
confidence: 99%
“…Blue light has been demonstrated to be beneficial for treating acute and chronic skin wounds, reducing inflammation, and promoting tissue regeneration [ 27 ]. Other studies have also reported that blue light holds some promise, particularly in the fight against excessive scarring and wound infections; however, it is crucial to consider the potential toxic and antiproliferative effects and to carefully consider the benefits and risks of using blue light to minimise the disturbances of skin physiology, which could result in impaired wound healing/closure and decreased scar breaking strength [ 28 ]. In this present study, a wavelength of 660 nm and a fluence of 5 J/cm 2 was used.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of the internal skin barrier is caused by internal factors, such as the metabolism of the cells and genetics [86][87][88][89]. The loss of the external skin barrier is caused by external factors, such as radiation, UVA (315-400 nm), UVB (280 to 315 nm), UVC (190-280 nm), infrared (IR) (750 nm-1000 µm), blue light (400-500 nm) [90,91] and chemicals [86,92,93]. An integral part of this process is the prolonged exposure of the skin to UVA, UVB or blue light causing photo-aging, characterized by loss of skin elasticity, wrinkling and skin hyperpigmentation, primarily on the face [69,86,94,95].…”
Section: Skin and Photo-aging 21 The Damaging Effects Of Uv Radiation...mentioning
confidence: 99%